2014
DOI: 10.1007/s11240-014-0659-1
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorodecalin-supported system enhances taxane production in hairy root cultures of Taxus x media var. Hicksii carrying a taxadiene synthase transgene

Abstract: Enhanced taxane production was observed in a hybrid, two liquid phases containing, cultures of Taxus x media var. Hicksii hairy root carrying a taxadiene synthase transgene, supported with liquid perfluorodecalin (PFD) in degassed or aerated form. The hairy root cultures were elicited with methyl jasmonate (MJ, 100 lM) or coronatine (COR, 1 lM), and fed with sucrose and L-phenylalanine. The root growth was not stimulated by PFD addition, irrespective of the day of its application (day 0 and 14). However, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 42 publications
3
34
1
2
Order By: Relevance
“…The results obtained in previous research performed by our group indicated that direct application of PFD to the culture system constitutes simple and efficient conditions for the enhancement of secondary metabolites production (Sykłowska-Baranek et al 2014, 2015a. In cultures of KT root line supplemented with PFD-aerated or degassed but without elicitors no lignan content was detected (Table 4).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 77%
See 3 more Smart Citations
“…The results obtained in previous research performed by our group indicated that direct application of PFD to the culture system constitutes simple and efficient conditions for the enhancement of secondary metabolites production (Sykłowska-Baranek et al 2014, 2015a. In cultures of KT root line supplemented with PFD-aerated or degassed but without elicitors no lignan content was detected (Table 4).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 77%
“…2d-f). In the previous investigation of our group performed in ATMA root line cultures the diminished biomass growth was noted as a result of PFD-aerated or degassed applied alone or in combination with 100 µM MeJa with a marked tendency of more pronounced growth suppression in PFD-aerated supported cultures (Sykłowska-Baranek et al 2015a). …”
Section: Pfd-phases Supported Cultures Of Atma and Kt Hairy Root Linesmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the txs synthase transgene has recently been successfully introduced in Taxus x media var. Hicksii, resulting in taxaneproducing transgenic hairy root cultures (Sykłowska-Baranek et al 2015).…”
Section: Introductionmentioning
confidence: 99%